Hidden Curriculum through the Book of Ta’lim Muta’allim for Strengthening Students’ Character at the Integrated Islamic Boarding School Ibnunnafis in Depok - Farid Maulana; Ai Fatimah Nur Fuad (ARRUS Journal of Social Sciences and Humanities, 2024)
This research analyzes the impact of the Ta’lim Muta’allim book as a hidden curriculum in learning processes at the integrated Islamic boarding school Ibnunnafis in Depok.The Implementation of the Ta’lim Muta’allim book is expected by the Islamic boarding school to enable students of having great characteristics and ethics for themselves and others. In order to analyze this topic, field research was chosen using a qualitative method that combines observation, interviews with teachers, students and alumni, and also collecting data from relevant documents and literatures. The result of this research indicates that the effectiveness of the implementation of the Ta’lim Muta’allim book as a hidden curriculum in students’ daily life at the boarding school significantly contributes to shape a young generation with strong characters and great morality. This contribution was driven by the distinctive materials of Ta’lim Muta’allim book focuses and emphasizes on the importance of everyday morals practiced among the closest people in the boarding school. This practice then has impact on the application of morals among wider community outside the boarding school.